2007
DOI: 10.1158/1078-0432.ccr-07-1218
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Dose-Finding Study of Weekly Docetaxel Followed by Flavopiridol for Patients with Advanced Solid Tumors

Abstract: Purpose: Flavopiridol is a cyclin-dependent kinase inhibitor that enhances docetaxel-induced apoptosis in a sequence-specific manner. In vivo, docetaxel must precede flavopiridol by at least 4 h to induce this effect. We conducted a phase I trial of weekly, sequential docetaxel followed 4 h later by flavopiridol in patients with advanced solid tumors. Experimental Design: Docetaxel at a fixed dose of 35 mg/m 2 was administered over 30 min, followed 4 h later by escalating doses of flavopiridol, ranging from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 14 publications
1
61
0
Order By: Relevance
“…Indeed, we have previously reported that inhibition of CDK-1 by its inhibitor, flavopiridol enhanced PBOX-induced apoptosis in CML cells by accelerating exit from G 2 /M (32). Sequential treatment with flavopiridol is also reported to enhance effects of docetaxel in patients with advanced solid tumours (33). Therefore, we decided to investigate if flavopiridol was capable of enhancing PBOX-induced apoptosis in PC3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we have previously reported that inhibition of CDK-1 by its inhibitor, flavopiridol enhanced PBOX-induced apoptosis in CML cells by accelerating exit from G 2 /M (32). Sequential treatment with flavopiridol is also reported to enhance effects of docetaxel in patients with advanced solid tumours (33). Therefore, we decided to investigate if flavopiridol was capable of enhancing PBOX-induced apoptosis in PC3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The best response was an extraordinary complete response in pancreatic cancer. Four prs were observed in various tumours 46 .…”
Section: Flavopiridolmentioning
confidence: 96%
“…Another phase I clinical study of sequential paclitaxel and Xavopiridol showed clinical activity in patients with esophagus, lung and prostate cancer including patients who had not (Schwartz et al 2002). The combination of Xavopiridol and docetaxel has been shown to be quite promising in several phase I clinical studies (Fornier et al 2007;El-Rayes et al 2006;Tan et al 2004). The combinations of Xavopiridol with gemcitabine and irinotecan (Fekrazad et al 2010), vorinostat (Dickson et al 2010), oxaliplatin and Xuorouracil/leucovorin (Rathkopf et al 2009), paclitaxel and carboplatin (George et al 2008), cisplatin and carboplatin ) and irinotecan (Shah et al 2005) were also assessed in various solid tumors in phase I clinical trials.…”
Section: Broad-range Inhibitorsmentioning
confidence: 99%